C_λ-semiconservative FK-spaces - Dagadur, I. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study C_λ-semiconservative FK-spaces for C_λ-methods defined by deleting a set of rows from the Cesaro matrix C_1 and give some characterizations.